The Overview of Safety Sign Supporting Road Area PT Angkasa Pura I Syamsudin Noor Banjarbaru Airport in 2022 - Mahda Halimah; Madschen Sia Mei Ol Siska Selvija Tambun (University of Technology Yogyakarta, 2023)
Abstract Safety signs are useful equipment to help protect the safety and health of workers and visitors while in the work environment. Safety signs can be useful for providing attention or warning of an alert attitude towards dangers that are invisible to the eye or warning of caution against actions that are not allowed. The purpose of this study is to find out how the description of the safety sign in the supporting road area of PT. Angkasa Pura I Syamsudin Noor Banjarbaru Airport. The type of research used is a descriptive research method. The method of data collection is carried out by direct observation with the Unit Safety Management System and Occopational Safety Health (SMS & OSH) and for the presentation of data, which is carried out using tables and accompanied by explanations. The results of this study show that in the parking area there are no signs for exit directions. In the front area of the administrative office building and in the mosque area, there are no signs for entry and exit signs. Meanwhile, in the cargo building area, the access road to get in and out of the box car is only one lane. It is recommended that the unit concerned should check further regarding safety signs and signs located in the supporting road area of Syamsudin Noor Airport. The relevant unit should be able to propose safety signs and related signs proposed by researchers for the safety and comfort of airport visitors in the area around the supporting road of Syamsudin Noor Banjarbaru Airport.